Prediction of temperature dependent wave dispersion and interaction properties in composite structures - Apalowo, R.K.; Ampatzidis, T.; Chronopoulos, D.; Ichchou, M.; Essa, Y.; De La Escalera, F.M. (2017)
Composite structures are widely used for aerospace and automotive applications. These operate within a broad temperature range varying between -100_C to 200_C for launch vehicles and -60_C to +50_C for aircraft and automotive vehicles. Hereby, the sensitivity of the wave propagation and interaction properties of a composite structure to the ambient flight temperature is investigated. A wave finite element (WFE) and finite element (FE) based computational method is presented by which the temperature dependent wave dispersion characteristics and interaction phenomenon in a composite structures can be predicted. Initially, the temperature dependent mechanical properties of the panel in the range of -100_C to 150_C are measured experimentally using the Thermal Mechanical Analysis (TMA). Temperature dependent wave dispersion characteristics of each waveguide of the structural system, which is discretised as a system of a number of waveguides joined by a coupling element, is calculated using the WFE approach. The wave scattering properties, as a function of temperature, is determined by coupling the WFE wave characteristics models of the waveguides with the full FE modelling of the coupling element on which defect is included. Numerical case studies are exhibited for two waveguides coupled through a coupling element.